Measurement of the production cross section of a W boson in association with two b jets in pp collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2017)
The production cross section of a W boson in association with two b jets is measured using a sample of proton-proton collisions at [Formula: see text] collected by the CMS experiment at the CERN LHC. The data sample corresponds to an integrated luminosity of 19.8[Formula: see text]. The W bosons are reconstructed via their leptonic decays, [Formula: see text], where [Formula: see text] or [Formula: see text]. The fiducial region studied contains exactly one lepton with transverse momentum [Formula: see text] and pseudorapidity [Formula: see text], with exactly two b jets with [Formula: see text] and [Formula: see text] and no other jets with [Formula: see text] and [Formula: see text]. The cross section is measured to be [Formula: see text]+[Formula: see text], in agreement with standard model predictions.